Polymeric Planar Microcavities Doped with a Europium Complex - Paola Lova; Marco Olivieri; Alba Surace; Gokhan Topcu; Mehtap Emirdag-Eanes; Mustafa M. Demir; Davide Comoretto (Crystals, 2020)
Organo-metallic europium complex tetrakis (dibenzoyl methide) triethylammonium (EuD4TEA) shows a sharp emission spectrum, which makes it interesting for photonic applications. In this work, we embedded it into all-polymeric planar microcavities and investigated the effect of the photonic environment on its emission spectrum. To this end, submicron-sized EuD4TEA crystals were loaded into a blend of polystyrene and carboxylic terminated polystyrene matrix, which served to stabilize the emitter in the polymer and to make the composite processable. The new composite was then casted by spin-coating as a defect layer in a polymeric planar microcavity. Spectroscopic studies demonstrate that fine spectral tuning of the cavity mode on the sharp organometal luminescence is possible and produces spectral redistribution of the fluorophore emission, along with a remarkable cavity quality factor.